1990
DOI: 10.1088/0022-3727/23/5/016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of TLD-100 glow peaks IV and V at elevated ambient temperatures

Abstract: This paper presents results obtained in a detailed study of the changes induced in TLD-1 00 glow peaks IV and V, during storage at 45 'C for up to 10 days.The modifications exhibited by the glow curve have been studied using a computer fitting programme to resolve the individual peak components. While peak V only experiences an increase in the number of traps, peak IV suffers marked modifications in position, intensity and width, revealing important changes in the trap structure, affecting to a different exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In LiF:Mg,Ti dosimeter, peaks 4 and 5 can be considered the main dosimetric glow-peaks. However, these peaks suffer from strong overlapping which increases the difficulties of the deconvolution process (Delgado and Gomez Ros, 1990). Therefore, it might be more accurate for dosimetric purposes to consider the sum of peaks 4 and 5 that has been shown to remain relatively constant at room temperature (Ben-Shachar and Horowitz, 1992).…”
Section: The Deconvolution Of the Glocanin Glow-curvesmentioning
confidence: 99%
“…In LiF:Mg,Ti dosimeter, peaks 4 and 5 can be considered the main dosimetric glow-peaks. However, these peaks suffer from strong overlapping which increases the difficulties of the deconvolution process (Delgado and Gomez Ros, 1990). Therefore, it might be more accurate for dosimetric purposes to consider the sum of peaks 4 and 5 that has been shown to remain relatively constant at room temperature (Ben-Shachar and Horowitz, 1992).…”
Section: The Deconvolution Of the Glocanin Glow-curvesmentioning
confidence: 99%
“…At higher heating rates, peaks 4 and 5 merge and become increasingly difficult to resolve [I I]. Other authors using a different glow curve analysis routine [28,29] and a rapid heating rate of 600°C min-' have studied the evolution of peaks 4 and 5 at 45 "C and 70 "C and have found growth of peak 5 and decay of peak 4. In these investigations the width of peak 4 was allowed to vary in the deconvolution procedure and it was found that the width of peak 4 became narrower and shifted to higher temperatures as a function of storage time.…”
Section: Long-term Fading Studiesmentioning
confidence: 99%
“…This phenomena has been theoretically studied by several authors [1][2][3][4][5][6], but no practical expressions have been given up to now.…”
Section: Introductionmentioning
confidence: 99%